Intravenous drugs abuse as the main risk factor of increasing hepatitis C infection prevalence in prisoners in Zenica, Bosnia and Herzegovina - Harun Hodžić; Amel Bajramović; Zarema Obradović; Mersiha Mahmić-Kaknjo (Medicinski glasnik, 2017)
Aim: To determine the prevalence of hepatitis C virus infection (HCV) among prisoners in Zenica prison, and to investigate the relation between HCV and risky behaviors: intravenous drugs use (IDU), tattooing, promiscuity. Methods: This cross-sectional study conducted at the High Security Penitentiary in Zenica involved 200 convicted persons who gave their consents for the research. Their blood was tested by AraGen Hepatitis C Test. Risky behaviors (IDU, tattooing, promiscuity) were tested by an anonymous self-administered questionnaire. Results: The prevalence of HCV was 13% (26/200). There was a statistically significant correlation of HCV infection and drug abuse before imprisonment (p=0.00), injection drug abuse before imprisonment (p=0.00), tattooing in prison (p=0.03) and having sex with homosexual partners (p=0.00). Conclusion: The prevalence of HCV in prisoners at Zenica prison was significantly higher than in the general Bosnia and Herzegovina population. Intravenous drugs use had highest risk for HCV infection among prisoners.
Keywords: tattooing; homosexuality; substance abuse